Effects of restrictions to Income Support on health of lone mothers in the UK: a natural experiment study - Srinivasa Vittal Katikireddi, PhD; Oarabile R Molaodi, PhD; Marcia Gibson, PhD; Ruth Dundas, MSc; Peter Craig, PhD (Elsevier, 2018)
Summary: Background: In the UK, lone parents must seek work as a condition of receiving welfare benefits once their youngest child reaches a certain age. Since 2008, the lower age limit at which these Lone Parent Obligations (LPO) apply has been reduced in steps. We used data from a nationally representative, longitudinal, household panel study to analyse the health effects of increased welfare conditionality under LPO. Methods: From the Understanding Society survey, we used data for lone mothers who were newly exposed to LPO when the age cutoff was reduced from 7 to 5 years in 2012 (intervention group 1) and from 10 to 7 years in 2010 (intervention group 2), as well as lone mothers who remained unexposed (control group 1) or continuously exposed (control group 2) at those times. We did difference-in-difference analyses that controlled for differences in the fixed characteristics of participants in the intervention and control groups to estimate the effect of exposure to conditionality on the health of lone mothers. Our primary outcome was the difference in change over time between the intervention and control groups in scores on the Mental Component Summary (MCS) of the 12-item Short-Form Health Survey (SF-12). Findings: The mental health of lone mothers declined in the intervention groups compared with the control groups. For intervention group 1, scores on the MCS decreased by 1·39 (95% CI −1·29 to 4·08) compared with control group 1 and by 2·29 (0·00 to 4·57) compared with control group 2. For intervention group 2, MCS scores decreased by 2·45 (−0·57 to 5·48) compared with control group 1 and by 1·28 (−1·45 to 4·00) compared with control group 2. When pooling the two intervention groups, scores on the MCS decreased by 2·13 (0·10 to 4·17) compared with control group 1 and 2·21 (0·30 to 4·13) compared with control group 2. Interpretation: Stringent conditions for receiving welfare benefits are increasingly common in high-income countries. Our results suggest that requiring lone parents with school-age children toseek work as a condition of receiving welfare benefits adversely affects their mental health. Funding: UK Medical Research Council, Scottish Government Chief Scientist Office, and National Health Service Research Scotland.